Analisis Kemampuan Metakognisi Siswa ditinjau dari Gaya Kognitif pada Materi Lingkaran Kelas VIII MTs Mathla’ul Anwar Pontianak - Nadila Nadila; Syarifah Fadillah; Sandie Sandie (Pusat Riset dan Inovasi Nasional, 2023)
This research implements a qualitative descriptive method, which aims to analyze students' metacognitive abilities in terms of cognitive style in class VIII circle material at MTs Mathla'ul Anwar Pontianak. Data is collected and described in the form of words in descriptive research. This research was conducted at MTs Mathla'ul Anwar Pontianak. This research data was collected through certain methods, namely, tests, questionnaires, interviews which were used to analyze students' metacognitive abilities, then processed into clear and easy to understand information. The data sources in this research were 4 class VIII students at MTs Mathla'ul Anwar Pontianak. The data collection techniques used in this research are measurement techniques, direct communication techniques and indirect communication techniques with data collection tools in the form of test questions, questionnaires, interview guides and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results showed that in general subjects who had a field independent cognitive style showed better abilities in solving problems compared to subjects who had a field dependent cognitive style.